Concussion in field hockey: a retrospective analysis into the incidence rates, mechanisms, symptoms and recovery of concussive injuries sustained by elite field hockey players. Issue 1 (17th September 2017) - Rossiter, Michael; Challis, Michael
Abstract : Objectives: To identify the incidence and mechanisms of concussion in elite Field Hockey in different age groups and also the postconcussion symptoms and recovery times. Methods: Data was collected retrospectively, for both training and matches, over a 12-month period from national level Field Hockey players across under-16, under-18, under-21, Development and Senior players. Mechanism of injury (including player role and field position), postconcussive symptoms and recovery times were recorded following a semistructured interview with each player. Additional information on training hours, matches and squad size were also recorded in order to calculate the incidence per 1000 match hours. Results: Of the 28 recorded cases, only 11 could be included in the study. Women had the highest incidence of concussion, with the majority being in the under-21 age group. Overall incidence varied from 3/1000 match hours in training to 0.02/1000 match hours in matches, with an overall incidence of 0–0.02/1000 match hours across all age groups. The most common mechanism of injury was collision with another player, followed by impact from a stick or ball Midfield and attacking forwards sustained the highest incidence of concussion. None of the concussed athletes wore protective headgear (there were no cases of concussion in goal keepers) and all occurred in open play rather than a penalty corner (when protective headgear is often worn). Postconcussion headaches and difficulty concentrating were the most commonly reported postconcussion symptoms. Average recovery time and return-to-play was 2–4 weeks. Conclusions: Due to the low numbers, only limited conclusions can be made, but it would appear that the risk of concussion in elite Field Hockey is low. As age and skill increases, the risk decreases. Postconcussion symptoms and average return-to-play times are similar to other sports. From this study, no conclusions can be made as to the role of protective headgear to reduce the risk of concussion.